Labor Unions and the Adoption of New Technology - Tauman, Y.; Weiss, Y. (Journal of Labor Economics, 1987)
The paper examines whether unionization by workers discourages the adoption of labor-saving techniques. This is done in the context of an oligopolistic industry with a small number of firms, some of which are unionized. We find that unionization can actually encourage the adoption of labor-saving technology, provided that the technological improvement is mild and that demand is sufficiently high (or demand elasticity sufficiently low). If there is an effective threat of entry that causes the union to moderate its wage demands, then unionization may encourage the adoption of new technology even at low levels of demand.